Detection of Human Polyomavirus 7 in Human Thymic Epithelial Tumors. Issue 2 (February 2015) - Rennspiess, Dorit; Pujari, Sreedhar; Keijzers, Marlies; Abdul-Hamid, Myrurgia A.; Hochstenbag, Monique; Dingemans, Anne-Marie; Kurz, Anna Kordelia; Speel, Ernst-Jan; Haugg, Anke; Pastrana, Diana V.; Buck, Christopher B.; De Baets, Marc H.; et al.
<x xml:space="preserve">Abstract</x> Introduction: Although the molecular genetics possibly underlying the pathogenesis of human thymoma have been extensively studied, its etiology remains poorly understood. Because murine polyomavirus consistently induces thymomas in mice, we assessed the presence of the novel human polyomavirus 7 (HPyV7) in human thymic epithelial tumors. Methods: HPyV7-DNA Fluorescence in situ hybridization (FISH), DNA-polymerase chain reaction (PCR), and immunohistochemistry (IHC) were performed in 37 thymomas. Of these, 26 were previously diagnosed with myasthenia gravis (MG). In addition, 20 thymic hyperplasias and 20 fetal thymic tissues were tested. Results: HPyV7-FISH revealed specific nuclear hybridization signals within the neoplastic epithelial cells of 23 thymomas (62.2%). With some exceptions, the HPyV7-FISH data correlated with the HPyV7-DNA PCR. By IHC, large T antigen expression of HPyV7 was detected, and double staining confirmed its expression in the neoplastic epithelial cells. Eighteen of the 26 MG-positive and 7 of the 11 MG-negative thymomas were HPyV7-positive. Of the 20 hyperplastic thymi, 40% were HPyV7-positive by PCR as confirmed by FISH and IHC in the follicular lymphocytes. All 20 fetal thymi tested HPyV7-negative. Conclusions: The presence of HPyV7-DNA and large T antigen expression in the majority of thymomas possibly link HPyV7 to human thymomagenesis. Further investigations are needed to elucidate the possible associations of HPyV7 and MG.